Flexible modular dwelling for rural environments; specific case: Cebadas – Ecuador [version 2; peer review: 2 approved] - Karina Elizabeth Cajamarca Dacto; Maikol Josueé González Espinosa; Dany Marcelo Tasan Cruz; Erick Fabricio Nieto Páez; Jean Carlos Montero Riofrio (F1000Research)
Background Sustainable modular dwelling design for rural areas should focus on creating healthy and economically accessible spaces, sensitive to local needs and integrating environmental, functional, sociological and technological aspects. Flexibility is essential to reduce the initial investment and allow future transformations, optimizing the recovery and reuse of materials. These houses must be adaptable, safe and have basic services, satisfying the needs and stages of families’ development. In Ecuador, poverty and energy inefficiency worsen the quality of life in rural areas. This project in the Cebadas parish proposes modular dwelling that applies bioclimatic and sustainable criteria, using local materials to improve habitability and promote the social and economic development of the community. Method The research approach is qualitative-quantitative. Qualitative, since it is necessary to identify the qualities of the sector, bibliographic exploration of guidelines and sustainable strategies. Quantitative, to evaluate the degree of affectation through a diagnosis of the study site and to provide efficient solutions that respond to the context and social reality. Results The spaces presented in the proposal respond to the spatial need for growth and expansion of the users of the sector, through 6 basic guidelines that this type of dwelling should have: Environment, Visual, Form, Function, Bioclimatic and Materials. Conclusions The flexible modular dwelling project for rural environments addresses complex housing needs, highlighting the flexibility and adaptability of an expandable module. It includes income generation with a duplex apartment, fosters communal and cultural life with public and commercial spaces, promotes tourism and rural development with landscape design and crops. In addition, it ensures sustainability through bioclimatic strategies and responsible use of resources.